An Analysis of Slot Dimension Changing in Dual band Rectangular Patch Microstrip Antenna with Proximity Coupled Feed - Nurista Wahyu Kirana (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
In this paper, the characteristics of dual band rectangular patch microstrip antenna using proximity couple feed are studied. It can be used for a wireless device that works on multiband frequency. The addition of slot and proximity feed used in order to obtain larger bandwidth and multiple frequency. Microstrip antenna is designed and simulated using software also used to analyze by changing the variable of microstrip slot’s dimension. The parameters are tested in this study include Voltage standing wave ratio (VSWR), return loss, gain, bandwidth and radiation patterns. From the simulation results, the best value of return loss antenna is -23,29 dB at 2,4 GHz with a slot width of 1 mm and 0,085 GHz bandwidth. At 3,7 GHz, the best value of return loss antenna is -23dB with a slot width of 2 mm and 0,12 GHz bandwidth. Afterwards, the best VSWR obtained on dual band microstrip antennas with proximity coupled feed is 1,14 and 5.53 dBi gain.Keywords: slot, bandwidth, proximity, return loss, gain.